Development of a wearable resonator mask for breathing rate monitoring - Yusnita Rahayu; Tasya Kirana; Jack Ping Soh (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
As one of the processes of patient care, diagnosis, and monitoring are the most important steps in the medical field. Sleep apnea is a problem that affects about 25 million Americans, and 80% of them go untreated because it is not identified. Monitoring has a big role in making patient treatment decisions. So this research aims to produce a wearable resonator mask that can work as a breathing rate monitor. The proposed resonator will use the relative humidity generated during the respiration process. The resonator uses a textile jeans material that is flexible, comfortable, and fits on a mask. Testing is carried out in 3 different positions; lying down, sitting, and standing. There is a difference in the percentage of RH produced from each position based on the difference in the frequency range produced. The proposed resonator operates well at 3.9 GHz.